EXPLORING PROJECT-BASED LEARNING FOR YOUNG LEARNERS IN ENGLISH EDUCATION - Didit Kurniadi; Ika Oktaria Cahyaningrum (PRODI PENDIDIKAN BAHASA INGGRIS INSTITUT PENDIDIKAN DAN BAHASA INVADA, 2023)
This research endeavors to bridge the existing gap in the literature by investigating the implementation of Project-Based Learning (PBL) in English education for young learners and its influence on their language acquisition and critical thinking abilities. Employing a mixed-methods approach, this study combines quantitative analysis of language proficiency tests with qualitative exploration of student perspectives and teacher insights to unveil the transformative potential of PBL in facilitating comprehensive language development and fostering essential cognitive competencies in young learners. The research findings offer compelling evidence that PBL serves as an effective instructional strategy, holding promise in augmenting language proficiency and nurturing vital cognitive aptitudes among young English learners. These valuable insights contribute to the advancement of educational practices and inspire innovative approaches to language teaching, ultimately empowering young learners to become confident communicators and astute critical thinkers in today's interconnected global landscape.